A longitudinal analysis of the overlap between violence and victimization among adults with mental illnesses. (30th December 2016) - Johnson, Kiersten L.; Desmarais, Sarah L.; Tueller, Stephen J.; Grimm, Kevin J.; Swartz, Marvin S.; Van Dorn, Richard A.
Abstract: Prior research suggests considerable overlap of violence perpetration and victimization among adults with mental illnesses. However, there has been no examination of how the likelihood of being a victim and/or perpetrator of violence may change over time, nor consideration of clinically-relevant factors affecting these transitions. In a pooled sample of adults with mental illnesses (N=3, 473) we employed latent transition analysis to: (a) determine prevalence of four violence and victimization classifications (i.e., non-victim/non-perpetrator, victim only, perpetrator only, and victim-perpetrator) over a 6-month period; (b) calculate the likelihood that adults with mental illnesses will remain in or transition between these classifications over time; and (c) assess the effects of recent substance use, psychiatric symptoms, and suicidal behaviors on transitions over time. At each time point, the majority of participants identified as non-victim/non-perpetrators, followed by victim-perpetrators, victims only, and perpetrators only. Analyses also revealed many individuals transitioned between classifications over time. These distinct pathways towards, and away from, violent outcomes were, in part, a function of recent violence and/or victimization, as well as substance use, psychiatric symptoms, and suicidal behaviors. Findings inform the identification of adults with mental illnesses at risk of violence and victimization and highlight points of intervention. Highlights: Experiences with violent outcomes vary widely among adults with mental illnesses. An individual's classification as a victim and/or perpetrator may change over time. Clinical characteristics are associated with changes in classification over time. Interventions targeting clinical characteristics may prevent violent outcomes.